2019
DOI: 10.1037/pas0000654
|View full text |Cite
|
Sign up to set email alerts
|

Personality in situations: Going beyond the OCEAN and introducing the Situation Five.

Abstract: The data presented in this manuscript were also used in the Manual of the proprietary test, The Big Five Inventory of Personality in Occupational Situations (Ziegler, 2014). Furthermore, the scales presented here have been referenced in a published book chapter (Horstmann, Rauthmann, & Sherman, accepted).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 79 publications
(146 reference statements)
1
66
0
2
Order By: Relevance
“…Persons may possess general tendencies to perceive and interpret situations, which are reflected in their behavior. As Horstmann, Ziegler, and Ziegler (2018;Ziegler & Horstmann, 2015;Ziegler et al, 2019) point out, assessing these tendencies-which are independent from "classic" (Big Five/Six) personality traits-may open up new avenues for personality assessments and the prediction of relevant outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Persons may possess general tendencies to perceive and interpret situations, which are reflected in their behavior. As Horstmann, Ziegler, and Ziegler (2018;Ziegler & Horstmann, 2015;Ziegler et al, 2019) point out, assessing these tendencies-which are independent from "classic" (Big Five/Six) personality traits-may open up new avenues for personality assessments and the prediction of relevant outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of situational taxonomies and measures, effects of situations have been examined more systematically. Situation characteristics that were assessed with standardized and validated measures allowed theoretically meaningful predictions of behavior in several instances (Brown et al, 2015;Gerpott et al, 2017;Parrigon et al, 2017;Rauthmann et al, 2014;Ziegler et al, 2019). Further, several situation dimensions have been explicitly linked to behavioral manifestations of personality traits (de Vries, Tybur, Pollet, & van Vugt, 2016;Parrigon et al, 2017;Rauthmann, Jones, & Sherman, 2016;Sherman et al, 2015).…”
Section: Situational Taxonomies and Measures Rauthmann And Colleaguesmentioning
confidence: 99%
“…As summarized in Figure 1, seven taxonomies of situation characteristics emerged in the last decade (Brown, Neel, & Sherman, 2015; Gerpott, Balliet, Columbus, Molho, & de Vries, 2018; Griffo & Colvin, 2019; Oreg, Edwards, & Rauthmann, 2020; Parrigon, Woo, Tay, & Wang, 2017; Rauthmann et al, 2014; Ziegler, Horstmann, & Ziegler, 2019). All were developed independently from each other with different approaches, levels of theory involvement, item pools, samples, and data-analytical strategies (though most approaches subscribed to factor-analytical techniques).…”
Section: The Knownsmentioning
confidence: 99%
“…Examples of empirical taxonomies include DIAMONDS (Rauthmann et al, 2014) and the Big Five framework (Griffo & Colvin, 2019). Examples of lexical taxonomies include CAPTION (with English adjectives; Parrigon, Woo, Tay, & Wang, 2017), Situation 5 (with German adjectives; Ziegler, Horstmann, & Ziegler, 2019), and Situation Six (with Hebrew adjectives; Oreg, Edwards, & Rauthmann, 2020). Examples of theoretical taxonomies include Situational Affordances for Adaptive Problems (SAAP; use of evolutionary theory; Brown, Neel, & Sherman, 2015) and the Situational Interdependence Scale (SIS; use of interdependence theory; Gerpott, Balliet, Columbus, Molho, & de Vries, 2018).…”
Section: The Knownsmentioning
confidence: 99%
“…That gap was filled by Rauthmann et al (2014) who developed a variety of typologies, e.g., the DIAMONDS taxonomy, which they have striven to integrate with other situation typologies in order to identify cross-study commonalities (Rauthmann and Sherman, 2018). Ziegler et al (2019) have shown that one of these typologies, the Situation Five, shows considerable independence from a Big Five measure of personality. This enables the separation of personality measures from those of the situation, and provides evidence that the situation measures add predictive power to personality measures, supporting the original Lewinian distinction between P and S (Funder, 2006).…”
Section: Reclaiming the Individualmentioning
confidence: 99%